JANENGAN SEBAGAI SENI TRADISIONAL ISLAM-JAWA - Akhmad Arif Junaidi (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2013)
This paper is based on the cultural reality of Javanese Muslim society especially in Islamic Javanese traditional music. The cultural expression of Islamic-Javanese music is very diverse and reflecting the diversity of the “face” of Islam that has been adapted to the local culture. Janengan’s Islamic Javanese traditional music is an expression from three different cultural music traditions: Javanese music tradition, Middle Eastern music traditions (Arabic), and currently has been developed with a combination of Western music such as pop. The combination of three different musical traditions creates a unique creativity in Javanese music character. The character also encourages the values covering musical values, cultural values, and religious values. Thematically, the Janengan’s lyrics contain a variety of Islamic teaching such as monotheism, shari’ah and sufism.